Memelihara Anak Yatim Perspektif Hadis - Meki Johendra; Sumiarti Sumiarti; Edriagus Saputra (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
This research is a library research using qualitative methods. This research aims to understand the hadith of the Prophet Muhammad related to caring for orphans. In this study, the primary sources are related classical hadith books, such as Sahih Bukhari, Sahih Muslim, Sunan Abu Daud, Sunan Nasa'i and others. Meanwhile, the secondary (supporting) sources of this research are books related to the study of caring for orphans. The results of this study can be concluded, that there are 10 hadiths that explain about caring for orphans and their virtues, which were narrated by Imam Bukhari, Imam Muslim, Abu Daud, Nasa'i, Ibn Majah, Tirmidhi, and Imam Malik. Understanding the hadith about caring for orphans and its virtues, that people who take care of orphans will get blessings from Allah and the Messenger of Allah. In addition, other virtues are obtained, namely getting abundant sustenance, getting self-comfort and getting intercession in the hereafter.